Locational investment signals in electricity markets - How to steer the siting of new generation capacity? - Anselm Eicke; Tarun Khanna; Lion Hirth (ZBW – Leibniz Information Centre for Economics, 2019)
The location of new power generation capacity has a significant effect on the need for transmission infrastructure. Newly constructed power plants that are located far from consumption centers increase network losses, investment, and potentially congestion. In addition, lack of public acceptance for transmission extension may increase the relevance of geographical steering of generation investments. The primary objective of this paper is to compare the regulatory instruments that provide locational investment signals. We cluster these instruments into the five groups locational electricity markets, deep grid connection charges, grid usage charges, capacity mechanisms, and renewable energy support schemes. We discuss properties of these instruments and then review their use in twelve major power systems, including a quantitative estimate of their strength. We find that most power systems use multiple instruments in parallel and that there is a lack of consensus regarding how to steer generation capacity. The results also indicate that the efficacy of many instruments is reduced due to a lack of credibility, low levels of transparency, and insufficient spatial and temporal granularity.
Additional information: Please cite as: Eicke, Anselm, Tarun Khanna & Lion Hirth (2020): “Locational investment signals in electricity markets: How to steer the location of new power generation capacity”, The Energy Journal 41(6), 281-304, https://doi.org/10.5547/01956574.41.6.aeic – The accepted manuscript (postprint version) is avaiable here: http://hdl.handle.net/10419/219543; More recent version: http://hdl.handle.net/10419/219543; More recent version: https://doi.org/10.5547/01956574.41.6.aeic
Keywords: Q48; Q41; 330; Investment signal; Generators; Network infrastracture; Locational steering; Regulation; Locational electricity market; Grid usage charge; Grid connection charge; Capacity mechanism; Renewable energy support scheme